Revealing Implementation of an Integrated Curriculum in Indonesian School. - Nurul Ulfa Nistiti (Department of English Language Education, UIN Sunan Ampel Surabaya, 2022)
The curriculum plays a very important role in the world of education as a guide for future educational goals so that it runs better and maximally. In the application of the curriculum, it is developed in schools to adapt to environmental conditions and needs, because these are related to each other in it and become a reference for all parties who play a role in implementing the applicable curriculum. The curriculum process includes planning, organizing, implementing, monitoring, and evaluating, developing a good curriculum certainly requires in-depth study and thought. Evaluation as the final process of a curriculum is used as a benchmark for curriculum achievement. Education is a human effort to improve knowledge, both obtained from formal and informal institutions. To achieve this, proper educational goals are needed. The purpose of education will determine success in the process of forming the human person, of course, balanced with other elements in education. The purpose of writing this article is to analyze the importance of the role of the curriculum in achieving educational goals. This study is a qualitative descriptive method. Descriptive qualitative research is research with data collected in the form of words and not numbers. This study has three objectives, namely (1) revealing the concept of an integrated curriculum in schools by a model that is suitable within a single discipline, (2) implementation of an integrated curriculum in schools by a model that is suitable within a single discipline, and (3) Evaluation of an integrated curriculum. in school by a model that is suitable within a single discipline.